THE USAGE OF DISEASE NAMES IN LITERATURE AND THEIR DERIVATION - Uraeva Darmon Saidakhmedovna; Bakhronova Matluba Akhmedovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In each language, medical terms, including lexemes representing the names of diseases, form a special layer of the language vocabulary, because such lexemes have their own, strong lingo cognitive basis. Such a basis for them is the universal conceptual semantics that exists in the thinking of speakers of every language, that is, the conceptual semantics of "disease". This article includes the derivation of disease names and the metabolization process.